Cutting Edges of Science Edification: The Power of Economy (Global Journal of Medical Research, 2015)
This article innovatively elaborates on two entirely useful and harmful angles of science education in building growing economy nationally and globally. Static economy-demolishing schooling versus accountable and moral economy-flourishing mentorship is delineated from a science edification philosophy. Generating moral figures and perceptions from scientific and educational discoveries must be globally pursued. This is key to maintaining an expanding nature for science-founded economy and to establishing national and international peace and prosperity.
Keywords: science; education; economy; global business; finance